Features of the investigation of intentional killings of servicemen which were committed during combating uses with the use of explosive explosives - Syvoded, Ivan (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
The article is devoted to the problem of the peculiarities of the investigation of premeditated murders of servicemen during hostilities. It is believed that this area is not yet sufficiently studied, which determines the relevance of the scientific research. The purpose of the study is to identify patterns of connections in the mechanism of investigation of premeditated killings of servicemen using explosive devices and explosives. It is noted that scientists have sufficiently studied the features of the initial stage of investigation of these crimes, but we believe that the investigation of premeditated killings of servicemen during hostilities using explosive devices and explosives has not been sufficiently addressed by scientists.According to criminological data, criminal violence has been escalating intensively in Ukraine over the last ten years. Thus, the number of registered killings during the period of hostilities in Ukraine has almost doubled in the last 5 years.Of particular concern is the increase in premeditated killings of servicemen in the area of the anti-terrorist operation, which are committed in military units while on guard duty, patrolling the territory and on a domestic basis. There are many cases of premeditated killings of servicemen, which are related to the concealment of a corpse, imitation of death during hostilities and more.According to the results of scientific analysis, it is safe to say that a significant number of murders of servicemen are committed with the use of explosives and mines and explosive devices as a result of shelling, hostilities, terrorist attacks.It is noted that certain problems have been identified in the conduct of certain investigative actions, in particular, the peculiarities of the scene inspection, examination of the corpse, interrogation of suspects and witnesses, investigative experiment, search measures to identify and detain wanted persons. Therefore, it is necessary to continue the scientific research in developing a mechanism for investigating these crimes in the context of hostilities.The conclusions state that under such conditions only coordinated, high-quality, prompt and timely primary investigative (investigative) and covert investigative (investigative) actions, the use of a full range of forensic methods, forensic capabilities, high professionalism of investigators, prosecutors, operatives, promotes and allows to reveal criminal offenses of this category.